The effect of various urban discharges on the microbiological water quality in catchment systems : an environmental health-related impact study - Mariette, Griesel (Bloemfontein: Central University of Technology, Free State, 2001)
The aim of this study was to assess the impacts that urban run-off, as well as effluent from two wastewater treatment works, from Bloemfontein city, had on the health-related microbiological quality of water in the Renoster Spruit sub-catchment, which forms part of the Modder River catchment (Free State province, South Africa). "Impact" on the microbiological quality of receiving waters was, for the purposes of this study, defined as the ability of faecally polluted urban discharges to overcome the natural assimilation capacity of receiving waters to the extent that the water quality became unfit for health-related domestic, recreation or agricultural use and water-related infections could therefore, be expected. The health-related microbiological quality of the various waters was investigated by using E. coli, C. perjringens spores and somatic coliphages as microbiological indicators. The natural background geometric mean levels for E. coli, C. perjringens spores and somatic coliphages in the Renoster Spruit were 85; 10; 3 per 100 mL, respectively. This indicated that the water was not suitable for untreated drinking or full contact recreation purposes, but suitable to treat for domestic use, and for irrigation of health-sensitive crops. The numbers of organisms of the selected indicator groups, increased significantly in the Renoster Spruit directly downstream from the newly constructed Sterkwater wastewater treatment works since treated effluent discharge commenced. The geometric mean levels for E. coli, C. perfringens spores and somatic coliphages increased to 13 686; 4 003 and 8 923 per 100 mL respectively, which indicated a noticeable impact on the microbiological quality of water in the Renoster Spruit. This was also an indication that Sterkwater could not maintain statutory microbiological levels in effluent for this study period. The numbers of indicator organisms in the Bloem Spruit system indicated heavy faecal pollution from diffuse urban run-off as well as effluent from the Bloem Spruit wastewater treatment works. Geometric mean levels for E. coli, C. perjringens spores and somatic coliphages were as high as 59 027; 402; 9 098 per 100 mL respectively, indicating a severe impact. The Bloem Spruit impacted the quality of water in the Renoster Spruit after confluence. The geometric mean levels for E. coli, C. pe,:fringens spores and somatic coliphages were as high as 2 240; 154 and 4 883 per 100 mL respectively. The water in this part of the Renoster Spruit was unfit for domestic, recreation and agricultural uses. Further downstream, the water quality improved to a quality suitable for fitness for agricultural uses, but still constituted a risk for other uses. The geometric mean levels for E. coli, C. perfringens spores and somatic coliphages decreased to 481 ; 51 and 922 per 100 rnL respectively. Water in the Modder River downstream from the Renoster Spruit confluence could be used for domestic (after limited treatment), recreation and irrigation of health-sensitive crops. The geometric mean levels for E. coli, C. perfrillgens and somatic coliphages were 39; 37 and 36 per 100 rnL respectively. The water of the Renoster Spruit, in the direct vicinity of Bloemfontein, was unfit for domestic, recreational and agricultural purposes. However, the microbiological quality of water in the Modder River, after confluence with the Renoster Spruit, did not reflect any impacts since the lower reaches of the Renoster Spruit appeared to have successfully assimilated the microbiological pollutant load from the urban discharges. From the study results, it appeared that the health-related microbiological quality of water in the Renoster Spruit deteriorated when compared to results from previous studies on the same waters. This implies that urban pollution of the Renoster Spruit is increasing. A catchment management plan, with a focus on environmental health, should be designed and implemented for the Renoster Spruit sub-catchment, in order to protect and promote the health of potential water consumers and other categories of water users.
Thesis
Keywords: Water quality; Microbiology